Public security in Rio de Janeiro: Reflections on the militarization of life - Kilduff, Fernanda; Mariana Nicolau Oliveira; de Souza Barbosa Maia , Viviane (Argumentum, 2020)
The purpose of this article is to present reflections on the militarization of the Public Security policy in Brazil and to analyze the process of remilitarization of Rio de Janeiro during the federal intervention in 2018. It is proposed to problematize the so-called “crisis of the state” that justified the renewed process of occupation of the Armed Forces in Rio's favelas, which resulted in a significant increase in the number of deaths under the banner of “law and order” and “citizen security”. It is affirmed that the militarization of life, territories, and Public Security is legitimized by a racist ideology that historically allows the control and neutralizes the extermination of the young black people and the population residents of the periphery of the large cities.Keywords: Public Security. Militarization. Structural Racism.